Ketanserin in essential hypertension: a double-blind, placebo-controlled study. - Cameron, H. A. (BMJ Group, 1985)
The antihypertensive effect of the selective serotonin antagonist ketanserin was examined in a double-blind, placebo-controlled, parallel group study in 20 patients with essential hypertension. After 7 weeks treatment with ketanserin (mean dose 71 mg/d) there was a significant fall of both systolic and diastolic blood pressure, as compared to placebo, with a peak effect of 19.1/9.1 mmHg lying (P less than 0.01/P less than 0.01), and 16.5/11.3 mmHg standing (P less than 0.01/P less than 0.01); twice daily dosage appeared satisfactory. Subjective side effects were similar in the ketanserin and placebo groups. Ketanserin is an effective antihypertensive drug of moderate potency when given twice daily, with no orthostatic effect.